Hydrogen peroxide treatment induces the transposition of an insertion sequence in Deinococcus radiopugnans DY59 - Shin, Eunjung; Noh, Hee Seong; Ye, Qianying; Lee, Sung-Jae (Frontiers in Microbiology, 2023)
In this study, Deinococcus radiopugnans DY59 exhibited reduced viability when exposed to 5 kGy gamma irradiation and 300 mM hydrogen peroxide (H2O2) MIC values on a TGY agar plate. From the 3.5 Mb genomic DNA sequence of strain DY59 (Dec. 2014), 31 IS (insertion sequence) elements of six IS families including IS1, IS4, IS5, IS66, IS630, and IS701 and five unclassified IS elements were detected. Upon induction of oxidative stress with 80 and 100 mM H2O2, the unique ISs of the IS4 family member were actively translocated into a carotenoid biosynthesis gene phytoene desaturase (QR90_10400), resulting in non-pigment phenotypic selection. Therefore, these active transpositions of a specific IS family member were induced by oxidative stress at 80 and 100 mM H2O2. Furthermore, D. radiopugnans DY59 exhibited extremely higher MIC values against H2O2 treatment. To explain this phenomenon, qRT-PCR was conducted to assess the expression levels of catalase and three LysR family regulators. Our findings indicated that the ISDrpg2 and ISDrpg3 elements of the IS4 family were actively transposed into the phytoene desaturase gene by H2O2 treatment via replicative transposition. However, high H2O2 resistance did not originate from the expression and activity of catalase and LysR family regulators.